Role of pancreatic stellate cells in chemoresistance in pancreatic cancer - McCarroll, Joshua A.; Naim, Stephanie; Sharbeen, George; Russia, Nelson; Lee, Julia; Kavallaris, Maria; Goldstein, David; Phillips, Phoebe A. (Frontiers in Physiology, 2014)
Pancreatic cancer is highly chemoresistant. A major contributing factor is the characteristic extensive stromal or fibrotic reaction, which comprises up to 90% of the tumour volume. Over the last decade there has been intensive research into the role of the pro-fibrogenic pancreatic stellate cells (PSCs) and their interaction with pancreatic cancer cells. As a result of the significant alterations in the tumour microenvironment following activation of pancreatic stellate cells, tumour progression and chemoresistance is enhanced. This review will discuss how PSCs contribute to chemoresistance in pancreatic cancer.